Pengembangan Sistem Informasi MBKM Terintegrasi Berbasis Prototyping Berorientasi Pengguna - Toto Supartono; Nunu Nugraha; Erlan Darmawan (Buffer Informatika, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) policy requires higher education institutions to manage student learning activities in an integrated and efficient manner. However, MBKM data management still faces several challenges, including unintegrated administrative processes, delayed document verification, and limited access to course recognition information. These issues reduce efficiency and hinder effective academic management. This study aims to develop an integrated MBKM student data management information system based on user needs. This study employs a prototyping approach that enables iterative system development through continuous user involvement, from requirement analysis to system evaluation. Data were collected through questionnaires involving 1,645 respondents and supported by interviews to identify system requirements. The results show that the developed system successfully integrates MBKM management processes, including program data, document management, student activities, and reporting within a web-based platform. Functional testing using black-box testing achieved a 100% success rate, while User Acceptance Testing (UAT) yielded an average score of 87.6%, indicating a very good level of user acceptance. This study contributes by proposing a user-centered prototyping-based model for developing integrated MBKM information systems, which enhances data management effectiveness in higher education institutions. The findings indicate that the proposed system is feasible for real-world implementation in higher education environments.